When work interferes with life - Reiner Rugulies (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
This issue of the Journal contains an article by Gynning et al (1) on the impact of work-life interference on burnout and job discontent in a sample of 1575 physicians in Sweden. The authors measured work-life interference and burnout at baseline in 2021, followed participants for one year, and then measured burnout again. Higher levels of work-life interference in 2021 were associated with an increased risk of high burnout in 2022, after adjustment for sex, occupational rank, family situation, work hours, overtime work, work with COVID-19 patients, and high burnout in 2021. The estimates for the association were substantial, with odds ratios of 3.67 [95% confidence interval (CI) 2.78-4.83] and 1.53 (95% CI 1.05-2.25) in the crude and the adjusted analysis, respectively. Work-life interference in 2021 was also associated with risk of job dissatisfaction and turnover intention in 2022. Whereas the design of the study was simple and straightforward, the researched phenomena, both the exposure − work-life interference − and the outcome − burnout − are anything but simple and straightforward. Work-life interference Work-life interference and related concepts, such as work-life balance or work-family conflict, have been viewed and understood differently, depending on historical and other contexts. In the beginning of the Industrial Revolution, the demand for a healthy balance between work and life might have been best expressed in the slogan "eight hours labor, eight hours recreation, eight hours rest", allegedly coined by the British textile manufacturer and social reformer Robert Owen (1771-1858). Although the link between number of working hours and work-life balance persisted in the 21st century − as illustrated in a review by Albertsen et al (2) on working hours and work-life balance published in this journal in 2008 − new aspects emerged, such as the role of gender and gender disparities. Albertsen et al reported in their review that long working hours were strongly associated with a risk of lower work-life balance among women, whereas among men the association was much less clear. Today, there is a substantial literature studying and critically discussing concepts such as work-life interference and work-life balance from a feminist and post-feminist perspective (3, 4). In recent years, a generational perspective has been added to the research on work-life interference. It has been argued that workers from Generation Y (Gen Y or Millennials), comprising those born between the early 1980s and the mid-to-late 1990s, and Gen Z, those born between the mid-to-late 1990s and early 2010s, are more sensitive about the negative effects of work on life and focused on protecting themselves from work that interferes with life than previous generations (such as Gen X or Baby Boomers) (5, 6). Other researchers, though, have strongly criticized the generational perspective and argue there are little-to-no generational effects and that the apparent differences between the generations are actually due to age and period effects (7). An important period effect might be that in this day and age, the distinction between work and life is becoming less clear compared to earlier days of industrialized societies. Whether this is good or not for workers' physical and mental health is not easy to answer. For many workers, and in particular but not limited to highly educated professionals (such as us, academic researchers), work is a major part of life and a key contributor to identity and self-esteem. The domains of work and life are often so much entangled that terms such as "interference" or "balance" may not be adequate to describe the relation between the two. The distinction between work and life may be further blurred because of technological advancements that allow a growing proportion of workers to work from home. Burnout The term burnout emerged in the 1970s from research on physical and mental exhaustion among volunteer workers in the USA (8). It gained popularity in particular due to the work by Christina Maslach, professor of psychology at the University of California at Berkeley, and the development of the Maslach Burnout Inventory (9). Maslach conceptualized burnout with three dimensions: emotional exhaustion, depersonalization (also termed cynicism), and reduced personal accomplishment (also termed reduced professional efficacy) (9). While the Maslach burnout inventory is by far the most widely-used instrument to assess burnout, it has also been criticized and controversially discussed, in particular with regard to the dimensions of depersonalization and reduced personal accomplishments (10, 11). Several other instruments, definitions, and conceptualizations of burnout have been proposed over the decades (12). A few years ago, the Network on the Coordination and Harmonisation of European Occupational Cohorts (OMEGA-NET) set up a panel of 50 researchers and healthcare professionals, with the aim of developing a consensual definition of occupational burnout. The results were published in the Journal in 2021 (12). The consensus definition was: "In a worker, occupational burnout or occupational physical AND emotional exhaustion state is an exhaustion due to prolonged exposure to work-related problems" (12). This brief consensus definition was the result of the panel`s impressive work that included reviews of the literature, critical discussions of the findings, and thoughtful deliberations. However, already in the next issue of the Journal, the consensus definition was challenged. In an editorial, Wilmar Schaufeli concluded that several questions regarding burnout still remain unsolved (13). One question is whether "exhaustion" is sufficient to define burnout, as the panel argued, or, as Schaufeli argued, that the burnout concept requires the inclusion of both the inability to spend effort at work (exhaustion) and the unwillingness to spend this effort (what Schaufeli termed "mental distancing"). Gynning et al (1) seem to have followed Schaufel`s reasoning and used in their study the Burnout Assessment Tool 12 (BAT-12) (14), a measurement that includes items both on exhaustion and mental distancing (see the supplementary material of their article for the wording of the items). Prevalence of burnout among physicians When one searches the Web of Science for the topics "work-life interference" OR "work-life balance", remarkably, the top-five cited articles that show up are all about burnout among physicians (15-19). It is further notable that each of these five articles had more than 1000 citations even though they were relatively recently published: in 2018 (two articles), 2016, 2015, and 2012, respectively. Thus, it seems fair to conclude that the study by Gynning et al addresses an area of great contemporary interest. Is prevalence of burnout particularly high among physicians compared to other occupational groups? The seminal article by Shanafelt et al (15) reported that 45.8% of the physicians showed at least one burnout symptom on the Maslach Burnout Inventory. For comparison with a US population control sample, Shanafelt and colleagues used a 2-item burnout measure that yielded a burnout prevalence of 37.9% among physicians and 27.8% among controls. Recently, Møller et al (20, 21) presented results from a burnout study that invited all 104 active vascular surgeons (including vascular surgeons in training) employed at a department of vascular surgery in a Danish hospital. Of those 104 surgeons, 85 completed the survey, yielding an astonishing response rate of 82%. Burnout was measured with the Copenhagen Burnout Inventory, which assesses exhaustion (but not mental distancing) on three separate scales: personal burnout (exhaustion without attribution to a cause), work-related burnout (exhaustion attributed to work), and client/patient-related burnout (exhaustion attributed to work with clients or patients (10). The prevalence of moderate or severe burnout was 28%, 16% and 4% for personal, work-related, and client/patient-related burnout, respectively (20). Compared to the burnout prevalence reported by Shanafelt et al (15) and Møller et al (20), the burnout prevalence reported by Gynning et al is rather low (4.5% and 5.8% in 2021 and 2022, respectively).